Effects of loading rate on gas seepage and temperature in coal and its potential for coal-gas disaster early-warning - Xu, Guang; Zhang, C.; Liu, X.; Wang, X. (2017)
The seepage velocity and temperature externally manifest the changing structure, gas desorption and energy release that occurs in coal containing gas failure under loading. By using the system of coal containing gas failure under loading, this paper studies the law of seepage velocity and temperature under different loading rates and at 1.0 MPa confining pressure and 0.5 MPa gas pressure, and combined the on-site results of gas pressure and temperature. The results show that the stress directly affects the seepage velocity and temperature of coal containing gas, and the pressure and content of gas have the most sensitivity to mining stress. Although the temperature is not sensitive to mining stress, it has great correlation with mining stress. Seepage velocity has the characteristic of critically slowing down under loading. This is demonstrated by the variance increasing before the main failure of the samples. Therefore, the variance of seepage velocity with time and temperature can provide an early warning for coal containing gas failing and gas disasters in a coal mine.